Rancang Bangun Smart Energy Meter Berbasis UNO dan Raspberry Pi - Agung Budi Muljono; I Made Ari Nrartha; I Made Ginarsa; I Made Budi Suksmadana (Jurnal Rekayasa Elektrika, 2018)
Smart energy meter (SEM) is developed to the transparency goal of energy consumption by consumers for tariff strategy. The tariff strategy is designed based on the type of consumer load that per-kWh energy price difference for linear and nonlinear loads. Energy conscious awareness is built by displaying all load power consumption information from consumer loads such as voltage, current, power factor, load properties, load type, power, volt-ampere distortion, power factor distortion, THD, current and voltage waveforms, and harmonic frequency spectrum. The SEM is designed using ZMCT103C and ZMPT101B for current and voltage sensors, respectively. The SEM security function uses the SW420 vibrating sensor, open/close bolt sensor on the chasing and electronic lock. The results show that error measurement of the voltage sensor, current sensor, and power factor are 0.8%, 1.5%, and 1.0% respectively. The SEM security works well as the information on maintenance and criminal actions are informed on screen and buzzer sound for criminal acts. The tariff strategy for linear and nonlinear loads is used to calculate the energy cost per-kWh. The details of load energy consumption are stored in a database.